Study of one-zone subcritical amplifiers of neutron flux involving enriched uranium - Babenko, V.A.; Gulik, V.I.; Jenkovszky, L.L.; Pavlovich, V.N.; Pupirina, E.A. (Вопросы атомной науки и техники, 2005)
We examine the main aspects of the construction of subcritical systems able to multiply neutrons from the
external source with emphasis on the choice of the neutron source and optimization of the parameters of the
subcritical system. We present results of our calculations of neutron flux amplification factor for the one-zone
spherical systems made up of the enriched uranium, water solution of the enriched uranium, and for the spherical
enriched uranium system with reflector. Розглянуто основні аспекти побудови підкритичних систем, здатних розмножувати нейтрони
зовнішнього джерела, що стосуються вибору джерела нейтронів і оптимізації параметрів підкритичної
системи. Представлено результати розрахунків коефіцієнтів посилення для однозонної сферичної системи зі
збагаченого урану, однозонної сферичної системи з розчину збагаченого урану у воді, а також для системи
збагаченого урану, що складається зі сферичної активної зони, і відбивача. Рассмотрены основные аспекты построения подкритических систем, способных усиливать нейтроны
внешнего источника, касающиеся выбора источника нейтронов и оптимизации параметров подкритической
системы. Представлены результаты расчетов коэффициентов усиления для однозонной сферической
системы из обогащенного урана, однозонной сферической системы из раствора обогащенного урана в воде,
а также для системы обогащенного урана, состоящей из сферической активной зоны и отражателя.